2017
DOI: 10.1017/s0025315417001266
|View full text |Cite
|
Sign up to set email alerts
|

Infanticide attacks and associated epimeletic behaviour in free-ranging common bottlenose dolphins (Tursiops truncatus)

Abstract: Infanticide is considered a conspicuous expression of sexual conflict amongst mammals, including bottlenose dolphins. Although reported previously in this species, confirmed cases of infanticide and associated epimeletic behaviour are very rare and their socio-behavioural context remains poorly understood. Here, we provide evidence of epimeletic and infanticide behaviours in free-ranging bottlenose dolphins in Galicia, NW Spain. After describing the observed events, we include a complete description of the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…Male alliances are responsible for violent kidnappings ("herding events") of non-pregnant females to increase their mating opportunities as well as of infanticides in different cetacean species such as the Amazon river dolphin (Inia geoffrensis) (14), Indo-Pacific humpback dolphin (Sousa chinensis) (15), killer whale (16), tucuxi dolphin (Sotalia guianensis) (17), and bottlenose dolphin (Tursiops spp.) (1,2,18,19). In Mysticetes, males humpback whales (Megaptera novaeangliae) have been reported escorting receptive females and threatening other males by thrashing of their flukes or signing as communication signals in the context of male competition (20).…”
Section: Introductionmentioning
confidence: 99%
“…Male alliances are responsible for violent kidnappings ("herding events") of non-pregnant females to increase their mating opportunities as well as of infanticides in different cetacean species such as the Amazon river dolphin (Inia geoffrensis) (14), Indo-Pacific humpback dolphin (Sousa chinensis) (15), killer whale (16), tucuxi dolphin (Sotalia guianensis) (17), and bottlenose dolphin (Tursiops spp.) (1,2,18,19). In Mysticetes, males humpback whales (Megaptera novaeangliae) have been reported escorting receptive females and threatening other males by thrashing of their flukes or signing as communication signals in the context of male competition (20).…”
Section: Introductionmentioning
confidence: 99%
“…Barnet et al 39 also reported that aggression from bottlenose dolphins might have led to the death of at least one Risso's dolphin (Grampus griseus), one long-finned pilot whale (Globicephala melas), one striped dolphin (Stenella coeruleoalba), and four short-beaked common dolphins (Delphinus delphis) on the southwest coast of England. More recently, an interspecific kill of a common dolphin by bottlenose dolphins was filmed and analyzed in detail in Northwest Spain 18 .Intraspecific aggression is commonly observed in bottlenose dolphin behavior repertories in many different contexts such as male competition, dominance, or female access for copulation, supported by wide field data [19][20][21][22] . However, many hypotheses have been proposed to explain the causal factors behind the aggressive interactions between bottlenose dolphins and other cetacean species, which have been reviewed by several authors 13,14,18,23 .…”
mentioning
confidence: 96%
“…In cetaceans, the focal adult often demonstrated protective behavior when observers attempted to separate the carcass, and in some cases of successful removal, the focal adult may resort to carrying an inanimate object as a surrogate to prolong the epimeletic behavior [ 12 , 16 ]. The focal adult–offspring pair is often accompanied by other conspecifics in the same social group, which may exhibit diverse behaviors, including but not limited to standing-by, supporting, socializing, or even aggressive behavior [ 10 , 17 , 18 , 19 ]. Acoustic records associated with epimeletic behavior of the highly vocal Tursiops truncatus have been reported where the nurturant adults emitted distress calls to seek aid from conspecifics [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%